Spearhead [compact disc, unabridged] : an American tank gunner, his enemy, and a collision of lives in World War II - Makos, Adam (Random House Audio, 2019)
Documents the story of a World War II tank platoon and gunner Clarence Smoyer, the gentle soldier behind the immortalized film footage of the iconic duel at the great cathedral in Cologne.